2019
DOI: 10.1017/gmh.2019.20
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms among women in Raqqa Governorate, Syria: associations with intimate partner violence, food insecurity, and perceived needs

Abstract: Background.Raqqa Governorate, Syria has recently been affected by overlapping conflicts related to the Syrian Civil war and occupation by ISIS, resulting in widespread displacement and disruption of economic livelihoods. However, little information is currently known about mental health needs and risk factors among women. Therefore, this study sought to examine potential risk factors for depressive symptoms among married women living in northern Syria.Methods.Data were collected between March and April 2018 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 47 publications
0
27
0
4
Order By: Relevance
“…Additionally, other analyses from the present study demonstrate that during the period of cash transfer delivery, some forms of past-three month intimate partner violence amongst a married sub-sample increased, although causality cannot be inferred due to the lack of counterfactual. [19] Nonetheless, such experiences of violence have been shown to be associated with a nearly three-fold increase in risk of depressive symptoms in this context [42], suggesting a potential dynamic relationship between cash assistance, intimate partner violence, and depressive symptoms in Raqqa Governorate, Syria.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, other analyses from the present study demonstrate that during the period of cash transfer delivery, some forms of past-three month intimate partner violence amongst a married sub-sample increased, although causality cannot be inferred due to the lack of counterfactual. [19] Nonetheless, such experiences of violence have been shown to be associated with a nearly three-fold increase in risk of depressive symptoms in this context [42], suggesting a potential dynamic relationship between cash assistance, intimate partner violence, and depressive symptoms in Raqqa Governorate, Syria.…”
Section: Discussionmentioning
confidence: 98%
“…Syrian refugee children are exposed to various traumatic events such as loss of a loved one, witnessing combat or life threat during war and flight ( Gormez et al, 2018 ). Other social risk factors during post-migration period such as child labor, family violence, and child marriage also negatively affect the psychosocial wellbeing of Syrian refugee children in Turkey ( El Arab & Sagbakken, 2019 ; Falb et al, 2019 ; Habib et al, 2019 ; Usta et al, 2019 ; Wringe et al, 2019 ). Associated with these risk factors, studies indicate higher estimates of PTSD, depression, and anxiety among Syrian refugee children compared to Turkish children.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by UNHCR in 2015 found that the highest risk for Syrian refugee children was psychological concern (51 %) followed by children dropped out of school (25 %) and child labor (11 %) ( UNHCR, 2015. p. 19 ). It is also important to mention that the risks identified in this study, including child labour ( Habib et al, 2019 ), child marriages ( El Arab & Sagbakken, 2019 ; Wringe et al, 2019 ) and domestic violence ( Falb, Blackwell, Stennes, Hussein, & Annan, 2019 ; Usta, Masterson, & Farver, 2019 ) in addition to the aforementioned higher risks, are factors which are likely to influence psychological wellbeing negatively.…”
Section: Vulnerabilities Of Refugee Children In Terms Of Health and Wmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite this increased investment in cash assistance in recent years, little is known about how cash influences the household dynamics and experiences of violence amongst women in humanitarian settings, including sexual exploitation or intimate partner violence (IPV). Such investigation is important as Syrian women often experience different forms of violence, including IPV [ 10 ] and baseline data from the present study indicated that a staggering one in three women in the sample had experienced IPV in the past 3 months [ 11 ]. In largely stable low and middle income countries, a recently completed systematic review of cash transfers, typically delivered as part of long standing social protection schemes, revealed that many cash transfer programs are associated with reductions of IPV; however, a small number of other programs had no or negative effect [ 12 ].…”
Section: Introductionmentioning
confidence: 99%